1981
DOI: 10.2134/agronj1981.00021962007300020021x
|View full text |Cite
|
Sign up to set email alerts
|

Water Deficit Effects on Water Potential, Yield, and Water Use of Cowpeas1

Abstract: Previous studies report conflicting results regarding the sensitivity of cowpeas to growth stage water deficits. Our 2‐year field study was designed to monitor the effects of water deficit imposed at three growth stages on the yield and water use of cowpeas (Vigna ungiculata (L.) Walp.). Six irrigation treatments were used to impose the water deficit including a well watered control treatment (WWW) and five deficit treatments (DWW, WDW, WWD, DWD, WDD). Cowpeas were grown on a sandy loam soil (coarse‐loamy, mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
8

Year Published

1983
1983
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 11 publications
2
23
0
8
Order By: Relevance
“…Thus, in 1998 the flowering time (about 43 days) of cowpea occurred during a period of high air temperatures (around 35 o C) (Figure 1), that contributed to reduce both observed and simulated grain yields by 12 and 19%, respectively. This was also noted by other authors (Roberts et al, 1978;Summerfield et al, 1978;Doto & Whittington, 1981;Shouse et al, 1981;Sivakumar et al, 1996;Craufurd et al, 1998).…”
Section: Resultssupporting
confidence: 85%
“…Thus, in 1998 the flowering time (about 43 days) of cowpea occurred during a period of high air temperatures (around 35 o C) (Figure 1), that contributed to reduce both observed and simulated grain yields by 12 and 19%, respectively. This was also noted by other authors (Roberts et al, 1978;Summerfield et al, 1978;Doto & Whittington, 1981;Shouse et al, 1981;Sivakumar et al, 1996;Craufurd et al, 1998).…”
Section: Resultssupporting
confidence: 85%
“…Para os efeitos observados com os cultivares BRS Guariba e BRS Pajeú verifica-se semelhança com a observação feita por Shouse et al (1981) os quais afirmam haver uma relação fonte dreno refletida por este componente de produção quando, no momento em que a massa de cem grãos é reduzida, indica que está ocorrendo limitação da produção na fonte. Este fato pode ocorrer em virtude do aumento no número de vagens, como no caso de tratamentos adequadamente irrigados ou pelo efeito do estresse hídrico sobre a fotossíntese ou, ainda, translocação de fotoassimilados em que, neste caso e segundo Costa et al (1997), o número de vagens por planta é inversamente proporcional à massa de cem grãos refletindo em uma compensação para limitações de tamanho do dreno, apesar do cultivar BRS Novaera se tenha mostrado totalmente contrário a esta observação apresentando o maior número de vagens por planta e, em contrapartida, maior massa de cem grãos.…”
Section: Resultsunclassified
“…The water stress effect showed small effect on relative water content, pod length, 100-seed weight, number of days to first flowering and number of days to first ripe pod, this was in agreement with Silva, 1978, who reported that seeds/pod and 100-seed weights were not significantly affected by either the water or the nitrogen fertilizer treatments. Babalola (1980) and Shouse et al (1980) observed similar effects during different phases of the crop's phenological cycle. Labanauskas et al (1981) reported that water deficiency during flowering and pod filling reduced productivity by 44% and 29%, respectively, but were not significantly affected by water stressed during vegetative period.…”
Section: Discussionmentioning
confidence: 66%
“…Yield increase in crops is a major objective of breeders; hence selecting for best genotypes in an environment where water stress is the most important factor limiting crop production. Cowpea suffer drought stress as a result of erratic rainfall due to climate change resulting in yield loss of up to 35-69% (Shouse et al, 1980;Fatokun et al, 2012). In general new cultivars are traditionally produced by plant breeders selecting directly for yield or yield components in specific environment.…”
Section: Introductionmentioning
confidence: 99%